Hemodynamic assessment of transitioning from parenteral prostacyclin to selexipag in pediatric pulmonary hypertension. (8th December 2022) - Colglazier, Elizabeth; Stevens, Leah; Parker, Claire; Nawaytou, Hythem M.; Amin, Elena K.; Becerra, Jasmine; Steurer, Martina; Fineman, Jeffrey R.
Abstract: Despite the increase in therapeutic options, parenteral prostacyclins remain the cornerstone in the medical management of pulmonary arterial hypertension (PAH). While the use of parenteral prostacyclins in pediatric patients is well documented, less is known about alternative drug delivery methods such as enteral administration. Given that parenteral routes of prostacyclin administration (IV or SC) are invariably accompanied by complicated logistics and lifestyle compromises, enteral prostacyclin administration represents an attractive treatment option. Selexipag (Uptravi®) was approved for adults PAH in 2015. There is limited data on the hemodynamic efficacy of transitioning from parenteral prostacyclins to selexipag, particularly in the pediatric population. We report 11 pediatric PAH patients who underwent this transition, in which 10 had complete cardiac catheterization data before and following the transition to selexipag. All patients/families reported an improvement in quality of life, and the transitions occurred without adverse effects. However, 3 of the 11 (27%) did not tolerate the transition; two for worsening hemodynamics, and one for acute right ventricular failure in the setting of an intercurrent illness. In addition, the transition to selexipag was associated with a modest increase in pulmonary vascular resistance index (6/10) and decrease in cardiac index (6/10) in some patients. Selexipag use in pediatric PAH represents a significant addition to our therapeutic arsenal, and its use provides a meaningful improvement in quality of life compared with other prostacyclin formulations. However, when goals of care include aggressive disease management, a decision between improved quality of life and possible adverse outcomes must be considered, and its substitution should include cautious, close, long‐term follow‐up.